1982
DOI: 10.1002/mpo.2950100410
|View full text |Cite
|
Sign up to set email alerts
|

Plasma phenylalanine: Tyrosine ratios during high‐dose methotrexate‐citrovorum “rescue”

Abstract: We have measured phenylalanine and tyrosine in the plasma of patients with osteogenic sarcoma undergoing chemotherapy with high-dose methotrexate (HDMTX) citrovorum factor rescue (CFR). During 14 treatments in six different patients, the phenylalanine to tyrosine ratio (PHE/TYR) at 21 to 38 hours was elevated over pretreatment levels. The observed increase in plasma phenylalanine is attributed to inhibition by MTX of the phenylalanine hydroxylase system of the liver, which is not folate-dependent and thus is n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

1986
1986
2002
2002

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 8 publications
2
7
0
Order By: Relevance
“…MTX also leads to alteration in the plasma levels of various amino acids, including an increase in the level of phenylalanine (PA) [5]. PA elevation leads to the depletion of tetrahydrobiopterin, a cofactor of tyrosine hydroxylase and tryptophan hydroxylase [6]. This leads to a decrease in the production of catecholamines and biogenic amine neurotransmitters such as homovanillic acid (HVA) and 5-Hydroxyindoleacetic acid (5-HIAA) [5] which may predispose to seizures.…”
Section: Discussionmentioning
confidence: 98%
“…MTX also leads to alteration in the plasma levels of various amino acids, including an increase in the level of phenylalanine (PA) [5]. PA elevation leads to the depletion of tetrahydrobiopterin, a cofactor of tyrosine hydroxylase and tryptophan hydroxylase [6]. This leads to a decrease in the production of catecholamines and biogenic amine neurotransmitters such as homovanillic acid (HVA) and 5-Hydroxyindoleacetic acid (5-HIAA) [5] which may predispose to seizures.…”
Section: Discussionmentioning
confidence: 98%
“…Patient D was studied during seven of eight treatments with HDMTX-CFR, which represented the third series of treatments this patient had received. Data in Table I show that mean pretreatment values for the ratio of FM concentrations of Phe/Tyr for this patient had changed from those reported during his first series of treatments, 5 to 6 years earlier (patient E) [2]. The general pattern of a decline after the initial peak, with a second peak at 7 1-96 hr, persisted throughout this series of treatments, as shown in Table 11.…”
Section: Concentrations Of Phe Andmentioning
confidence: 69%
“…This chemotherapy did not similarly perturb the concentrations of other plasma amino acids, as measured by standard amino acid analysis. Extension of the study revealed increases above pre-treatment values of Phe/Tyr ratios 24 hr after the beginning of the 6-hr infusion of HDMTX in each of five additional patients [2].…”
Section: Introductionmentioning
confidence: 97%
“…Although the focus of the programme is to screen for classic PKU, we have examined the registry of outcomes to determine if the implementation of ratio screening has aVected the number of cases classified as variant. Before implementation, an average 21 variants were logged per year (range [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. In the 12 month period following implementation of ratio screening, 12 variants were logged.…”
Section: Population Screeningmentioning
confidence: 99%
“…3 5-9 In the past, the phenylalanine:tyrosine ratio has been used to identify PKU carriers, [10][11][12][13][14] diVerentiate between PKU and non-PKU hyperphenylalanemia, 15 and monitor methotrexate cancer treatment. 16 …”
mentioning
confidence: 99%